2020
DOI: 10.1177/0300060520919592
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of matrix metalloproteinase 9 (MMP9)/tissue inhibitor of metalloproteinase 1 (TIMP1) and MMP2/TIMP2 ratios may be involved in lipopolysaccharide-induced acute lung injury

Abstract: Objective This study aimed to examine the changes and significance of matrix metalloproteinase 9 (MMP9), MMP2, tissue inhibitor of metalloproteinase 1 (TIMP1), and TIMP2 in rats with lipopolysaccharide (LPS)-induced acute lung injury (ALI). Methods Wistar rats were randomly divided into a control group (injected with saline) and an ALI group (injected with LPS), then subdivided into four time points (2, 6, 12, and 24 hours). Serum tumor necrosis factor alpha and interleukin-6 levels were detected by ELISA to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
1
21
0
1
Order By: Relevance
“…MMP-9 also has a cleavage effect on the ligand, CL8, that promotes the chemotaxis of neutrophils ( 37 ). In addition, MMP-9 acts as a gelatinase to hydrolyze the basement membrane and extracellular matrix of the blood vessels, directly impacting the structure of the respiratory tract and lungs ( 12 , 38 ). Thus, MMP-9 activity was also measured in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 also has a cleavage effect on the ligand, CL8, that promotes the chemotaxis of neutrophils ( 37 ). In addition, MMP-9 acts as a gelatinase to hydrolyze the basement membrane and extracellular matrix of the blood vessels, directly impacting the structure of the respiratory tract and lungs ( 12 , 38 ). Thus, MMP-9 activity was also measured in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HCC derived IL1A and TGFA appear to be promoting upregulation of TME-derived MMP9 and MMP2 , respectively. TIMP2 and TIMP1 are specific inhibitors of MMP2 and MMP9 , respectively ( Chen et al, 2020 ). MMP2 degrades ECM components of the basement membrane and facilitates tumor invasion while TIMP2 regulates MMP2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…e ECM is the main structural component of the alveolar-capillary membrane, which not only plays a mechanical-supporting and mechanical-connecting role between cells but is also important in maintaining normal Evidence-Based Complementary and Alternative Medicine tissue structure and function [9,32,33]. Previous work has shown that ECM metabolic disorders are involved in the pathophysiological process of ALI and chronic lung injury [34,35]. MMPs are proteolytic enzymes that rely on the metal ions zinc and calcium and use ECM components as hydrolysis substrates; they play an important role in maintaining the normal transformation of ECM, tissue damage and repair, inflammatory response, and other pathophysiological processes [11,12,36].…”
Section: Discussionmentioning
confidence: 99%
“…The ECM is the main structural component of the alveolar-capillary membrane, which not only plays a mechanical-supporting and mechanical-connecting role between cells but is also important in maintaining normal tissue structure and function [ 9 , 32 , 33 ]. Previous work has shown that ECM metabolic disorders are involved in the pathophysiological process of ALI and chronic lung injury [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%